Determination of biogenic amines in different types of cheese by high-performance liquid chromatography - Cunha, Fernanda Lima (2012)
This study aimed at detecting and quantifying biogenic amines (cadaverine, spermidine, histamine, putrescine and tyramine) in four different types of cheese using high-performance liquid chromatography (HPLC). For this study, ten samples of gouda, minas, mozzarella and prato, four types of cheese, were purchased in retail markets of Rio de Janeiro. Biogenic amines were previously extracted and derivatizated; then, these amines were detected and quantified by HPLC-UV. For assessing differences among the analyzed cheeses, data were submitted to Anova and Tukey’s test. Minas cheese showed the lowest amount of amine (24.26 mg.kg-1), and the highest contents (489.15 mg.kg-1) were found in gouda. As for the investigated biogenic amines, tyramine showed the highest concentrations (623.60 mg.kg-1), and spermidine was found at the lowest concentration (0.80 mg.kg-1) in all four types of cheese. This study indicates that gouda seems to demand a much more careful monitoring of biogenic amines in the analyzed cheese samples. Also, the methodology was effective for detecting and quantifying biogenic amines in all studied cheese samples.